Research and implementation of the IBN for cloud-network convergence service of operators - Xin ZHANG (Dianxin kexue)
Faced with the development of cloud computing technology and the increasing business needs, cloud-network convergence has become the inevitable choice of network architecture reform.The era of cloud-network convergence brought great challenges to the traditional network operation and maintenance, and the network needs to evolve to a more intelligent and convenient mode.The intent-based networking(IBN), which is widely studied by the scholars, has become the best choice to solve this problem.The development process, architecture and key steps of IBN were introduced.Combined with the needs of operator’s services, the business scenario of cloud-network convergence was taken as an example to analyze the implementation process of IBN for cloud-network convergence.It is expected to provide a reference for the future practice of IBN and cloud-network convergence services.